Perbedaan Keterampilan Menulis Deskripsi dengan Menggunakan Pendekatan Kontekstual dan Metode Quantum Learning Siswa Kelas XI SMAK Padang - Ferlin, Dini; Atmazaki, Atmazaki; Amir, Amril (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purpose of this study was (1) to describe a class XI student skills in writing descriptions SMAKPA using a contextual approach, (2) describe a class XI student skills in writing a description SMAKPA using quantum learning, (3) describe differences in students' skills in writing SMAKPA XI description of the approach and methods of quantum contextual learning. Sampling in this study was done by using a sample aims (purposive sample) of class XI SMAKPA, which is registered in the academic year 2011/2012. The instruments used in the form of written descriptions of performance tests. The study's findings that there are significant differences between the classes and the class contextual approach that uses quantum learning method to learning to write a description of 4.56.